2021
DOI: 10.1016/j.omtn.2021.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA RBPMS inhibits bladder cancer progression via miR-330-3p/RAI2 regulation

Abstract: Bladder cancer is a severe cancer with high mortality because of invasion and metastasis. Growing evidence has revealed that circular RNAs play critical roles in biological function, which is closely connected to proliferation and invasion of bladder cancer. In our study, we employed qRT-PCR, RNA fluorescence in situ hybridization (FISH), 5-ethynyl-2 0 -deoxyuridine (EdU), CCK-8, Transwell assays, luciferase reporter assays, xenografts, and live imaging to detect the roles of circular RNA binding protein with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 45 publications
2
33
0
Order By: Relevance
“…Collectively, upregulation of circRIMS1 expression could facilitate EMT in BCa. In vitro studies supported a relationship between dysregulated circRNAs and EMT in BCa, including circ0006332, circMTO1, circ5912, circFUT8, circ100984, and circRBPMS, along with upregulation of mesenchymal marker expression, including N-cadherin and vimentin ( Li et al, 2019a ; Li Y. et al, 2019 ; Su et al, 2019a ; He Q. et al, 2020 ; Tong et al, 2020 ; Yang et al, 2021 ). These findings demonstrate that circRNAs may be therapeutic targets, and the development of tools such as CircInteractome ( Dudekula et al, 2016 ) has improved the potential to develop siRNAs that are able to selectively inhibit circRNAs of interest.…”
Section: Circular Rnas and Bladder Cancermentioning
confidence: 79%
“…Collectively, upregulation of circRIMS1 expression could facilitate EMT in BCa. In vitro studies supported a relationship between dysregulated circRNAs and EMT in BCa, including circ0006332, circMTO1, circ5912, circFUT8, circ100984, and circRBPMS, along with upregulation of mesenchymal marker expression, including N-cadherin and vimentin ( Li et al, 2019a ; Li Y. et al, 2019 ; Su et al, 2019a ; He Q. et al, 2020 ; Tong et al, 2020 ; Yang et al, 2021 ). These findings demonstrate that circRNAs may be therapeutic targets, and the development of tools such as CircInteractome ( Dudekula et al, 2016 ) has improved the potential to develop siRNAs that are able to selectively inhibit circRNAs of interest.…”
Section: Circular Rnas and Bladder Cancermentioning
confidence: 79%
“…Fu et al reported that RBPMS inhibited the growth and migration of breast cancer cells by repressing AP-1 signaling [ 21 ]. Additionally, reduced levels of RBPMS have been documented in bladder cancer and multiple myeloma cell lines [ 56 , 57 ]. However, the biological role of RBPMS in ovarian cancer has not been previously studied.…”
Section: Discussionmentioning
confidence: 99%
“…As various RBPMS splice variants have been reported, future research should elucidate the specific splice RBPMS isoform responsible for the reported biological effects as well as how this regulation of RBPMS downstream targets occurs. Importantly, Yang et al recently reported that the low abundance of a circular RBPMS correlated with aggressive phenotypes in bladder cancer [ 57 ]. Increased levels of this circular RNA suppressed cell proliferation, invasion, and migration by directly targeting miR-330-3p and retinoic acid induced 2 axis (RAI2) [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tong et al suggested that circ_100984/miR-432-3p axis modulated c-Jun/YBX-1/ÎČ-catenin feedback loop to influence EMT and thus promote tumor progression [ 140 ]. CircRBPMS reduced the inhibition of RAI2 by sponging miR-330-3p, thereby suppressing the ERK signaling pathway and inhibiting the EMT process to repress BC progression [ 141 ]. Tan et al proved that circST6GALNAC6 inhibited EMT and BC metastasis partly via the miR-200a-3p/STMN1axis [ 142 ].…”
Section: Expression and Biological Functions Of Circrnas In Bcmentioning
confidence: 99%
“…Similarly, circRGNEF is upregulated in BC tissues, and its quantities are correlated with tumor size, grade, and lymph node metastasis [ 104 ]. In addition, circZFR, circTFRC, hsa_circ_0068871, circ_0067934, circPTK2, circINTS4, circCEP128, circSEMA5A, circVANGL1, andcircEHBP1 [ 31 , 106 , 107 , 121 , 126 , 127 , 162 , 169 , 178 , 179 ], which are overexpressed in BC tissues, and ciRs-6, hsa_circ_0077837, circCDYL, circFUT8, circPTPRA, circ_0071662, circFOXO3, circFAM114A2, circUBXN7, and circRBPMS [ 111 , 116 , 130 , 133 , 141 , 144 , 170 , 180 , 181 , 182 ], which are downregulated in BC tissues, are also reported to be associated with many clinicopathological features in BC ( Table 4 ).…”
Section: Relationships Between Circrnas Quantities and Clinicopathologic Features In Bcmentioning
confidence: 99%